Case report: long-term sustained remission in a case of metastatic colon cancer with high microsatellite instability and KRAS exon 2 p.G12D mutation treated with fruquintinib after local radiotherapy: a case report and literature review - Wang, Ruiqi; Cong, Dan; Bai, Yuansong; Zhang, Wenlong (Frontiers in Pharmacology, 2023)
To demonstrate the efficacy of fruquintinib administration after local radiotherapy in a patient with metastatic colon cancer with high microsatellite instability and the KRAS exon 2 p.G12D mutation. The patient was administered four cycles of pembrolizumab intravenous infusion and achieved stable disease as the best outcome. He was then underwent follow-up concurrent radiochemical therapy (local DT4600cGy/23f/32d radiotherapy, and S-1 to increase sensitivity to radiotherapy), but this had little efficacy. Following this, he was administered fruquintinib and achieved sustained partial remission. At the time of last follow-up, the patient was in continuous remission for 30 months. Administration of fruquintinib after local radiotherapy may be an effective treatment for specific populations with metastatic colorectal cancer.